A Study on the Application of Shore-Side Power as a Method to Reduce the Emissions of Greenhouse Gases by Cruise Ships - Mislav Rogosic; Tatjana Stanivuk; David Lucaci (Journal of Marine Science and Engineering)
The essence of this work is to explore the potential of shore-side power as a sustainable and efficient solution for mitigating greenhouse gas emissions from passenger ships during their berthing periods in ports. Cruise ships—including both cruise liners and ferries—are significant contributors to port-based emissions because they rely on onboard auxiliary engines to generate power while docked. This practice results in the continuous release of greenhouse gases, such as carbon dioxide, and other pollutants, including nitrogen oxides and sulfur oxides, which contribute to environmental degradation and pose public health concerns in port cities. The objective of this study is to highlight the critical role of shore-side power in decarbonizing the maritime industry and in helping achieve global climate targets. By addressing environmental, technical, and economic aspects, the research aims to provide a comprehensive framework for decision-makers, port authorities, and shipping companies to adopt this technology as a key measure for reducing emissions from cruise ships. Furthermore, this study investigates the multifaceted impacts of shore-side electricity—focusing on its long-term environmental, economic, and social implications—by analyzing case studies from ports that have successfully implemented this technology and by examining the barriers to its broader adoption. Ultimately, this research seeks to provide actionable insights for policymakers, port authorities, and shipping companies.